Oral Cancer Awareness of Tertiary Education Students and General Public in Singapore - Pujan Rai; Charlene E. Goh; Francine Seah; Intekhab Islam; Wendy Wang Chia-Wei; Philip Martin Mcloughlin; John Ser Pheng Loh (Elsevier, 2023)
ABSTRACT: Objectives: Oral cancer confers high morbidity and mortality rates. Late diagnosis of oral cancer is linked to a lack of awareness of its existence and known risk factors. The purpose of this survey was to examine the knowledge and awareness of oral cancer amongst different groups in Singapore. Methods: A self-administered questionnaire (including questions on awareness, risk factor knowledge, and health beliefs about oral cancer) was distributed to undergraduate students from the medical and dental schools and other faculties at the National University of Singapore, as well as the general public. Results: A total of 470 responses were analysed. Both medical and dental students were almost universally aware of the disease and correctly identified recognised risk factors for oral cancers. Dental students had a significantly higher level of knowledge of chewing betel quid as a risk factor than medical students (98% vs 74%; P < .0001), although 1 in 10 dental students did not identify alcohol as a risk factor. In contrast, undergraduate students from other faculties were the least aware of oral cancer (62%). Within the general public, knowledge of the risk factors of oral cancer aside from smoking was low, with only 41% aware of viruses as a possible aetiology. However, the younger population group, aged 18 to 34 years old, in general had better knowledge of the risk factors of oral cancer compared with older participants. Conclusions: There is a general lack of awareness about oral cancer and its associated risk factors amongst certain cohorts of the Singapore population. There exists room for further targeted education.